Efficacy and safety of continuous radiofrequency thermocoagulation plus pulsed radiofrequency for treatment of V1 trigeminal neuralgia: A prospective cohort study. Issue 44 (November 2016) - Yao, Peng; Hong, Tao; Zhu, Yong-qiang; Li, Hong-xi; Wang, Zhi-bin; Ding, Yuan-yuan; Ma, Jia-ming; Pan, Shi-nong
Abstract : Abstract: Patients may develop serious eye complications after continuous radiofrequency thermocoagulation (CRF) for V1 (ophthalmic division) trigeminal neuralgia (TN) at a higher temperature. Therefore, the temperature of clinical CRF for V1 TN has long been disputed, but there have few reports been found about how to achieve satisfactory pain relief, reduce the incidence rates of complications, and shorten the recovery time after CRF for V1 TN. To observe whether pulsed radiofrequency (PRF) can lead to increased rate in pain relief, reduced rate of complications, or shortened recovery time after CRF is used to treat V1 idiopathic trigeminal neuralgia (ITN). The prospective cohort study enrolled 56 patients with V1 ITN from May 2012 to April 2015. The patients were randomized into 2 treatment groups as follows: CRF only (group A, n = 28) and CRF plus PRF (group B, n = 28). The patients were followed 3 years up for pain relief, complications, and health-related quality of life (HRQoL). All the patients in either group achieved satisfactory pain relief at discharge. After treatment, patients completely pain free in group A and group B accounted for 81.6%, 92.0% at 1 year, 68.4%, 92.0% at 2 years, and 68.4%, 83.6% at 3 years, respectively. The pain relief rate was higher in group B patients than in group A, but the difference was not statistically significant. During the follow-up period, 9 (32.1%) patients in group A and 2 (7.1%) patients in group B developed recurrence ( P  < 0.05). Eleven patients in group A occurred corneal hypoesthesia and with recovery time was 11.9 ± 7.5 (4–18) months versus 3 patients in group B with recovery time was 3.4 ± 2.5 (2–6) months, the differences of incidence rate and recovery times were all significant ( P  < 0.05) between groups A and B. The mean scores of HRQoL in group B patients were higher than that in group A patients ( P  < 0.05). PRF after CRF results in decreased recurrence of V1 TN, reduced numbers of corneal hypoesthesia, shortened recovery time, and increased HRQoL scores. Its clinical use is recommended.